2021
DOI: 10.1038/s41467-021-20993-z
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channel ITPR2 and mitochondria–ER contacts promote cellular senescence and aging

Abstract: Cellular senescence is induced by stresses and results in a stable proliferation arrest accompanied by a pro-inflammatory secretome. Senescent cells accumulate during aging, promoting various age-related pathologies and limiting lifespan. The endoplasmic reticulum (ER) inositol 1,4,5-trisphosphate receptor, type 2 (ITPR2) calcium-release channel and calcium fluxes from the ER to the mitochondria are drivers of senescence in human cells. Here we show that Itpr2 knockout (KO) mice display improved aging such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(120 citation statements)
references
References 68 publications
4
116
0
Order By: Relevance
“…In line with increased evidence of the role of calcium fluxes within the cell and specifically between ER and mitochondria 46,61,62,144,145 , calcium signalling appears to be an interesting candidate to mediate the senescence phenotype. In human endothelial cells and MEFs, replicative senescence is characterized by an increased MERCs number and a subsequent accumulation of mitochondrial calcium 46,146 . Accordingly, replicative senescent neurons display also an increased transfer of calcium from the ER to mitochondria accompanied by an upregulation of MCU expression 147 .…”
Section: Mercs Regulate Cellular Senescencementioning
confidence: 77%
See 1 more Smart Citation
“…In line with increased evidence of the role of calcium fluxes within the cell and specifically between ER and mitochondria 46,61,62,144,145 , calcium signalling appears to be an interesting candidate to mediate the senescence phenotype. In human endothelial cells and MEFs, replicative senescence is characterized by an increased MERCs number and a subsequent accumulation of mitochondrial calcium 46,146 . Accordingly, replicative senescent neurons display also an increased transfer of calcium from the ER to mitochondria accompanied by an upregulation of MCU expression 147 .…”
Section: Mercs Regulate Cellular Senescencementioning
confidence: 77%
“…Concerning ITPR-GRP75-VDAC complex, GRP75 overexpression leads to increased replicative lifespan through downregulation of RAS and reduced phosphorylation of ERK2 118,119 and ITPRs promote cellular senescence 46,61,62 , as it will be further discussed below.…”
Section: Merc Components Modulate Key Senescence Featuresmentioning
confidence: 97%
“…More recent studies also showed that lowering endoplasmic reticulum (ER)-mitochondria contact by ablating the Itpr2 calcium channel in mice lowers the number of age-related senescent cells and the levels of several SASP factors, resulting in an extension of health span and lifespan 57 . However, it is unclear if these effects are due to reduced mitochondrial calcium overload, diminished ER-mitochondrial contacts, or some combination of both.…”
Section: Metabolic Drivers Of Senescencementioning
confidence: 99%
“…Indeed, Ca 2+ may play a role in this respect. Aside from cytochrome c and cognate apoptogenic agents, depolarized mitochondria initiate Ca 2+ waves and trigger the depolarization of surrounding mitochondria (Pacher and Hajnóczky, 2001;Ziegler et al, 2021). Actually, the propagation of waves of released cytochrome c have been reported during apoptosis (Lartigue et al, 2008;Cheng and Ferrell, 2018).…”
Section: Local and Temporal Activation Of Caspases In Non-apoptotic Processesmentioning
confidence: 99%